قضية الشرق و الغرب: قراءة في الصراع الحضاري - Yaacob, Adli (الجامعة المانيا, 2014)
The clash of civilization between East and West had begun even before the era of Islam. Fierce wars and conflicts continued without any clear victor or loser. After the emergence o f Islam as a super power the conflict took a religious tone to become a conflict between Islam and Christianity. The Roman Empire which was bordering the Islamic territories were always waging wars on the Caliphate. The conflict was prolonged during the Cr usade wars and after their defeat, after so many years it emerged again after the fall of the Ottoman Empire. Many Muslim countries were subjected to conquer of the Western powers. Even after many countries had already gained independence, Palestine remain ed under Israel to this day. Western powers remain cautious of the Muslim countries which on occasions led to the spill of blood of the innocents through wars which were either instigated or initiated by the Western powers. The war between Iran and Iraq, t he toppling of the leadership in Iraq and the invasion of Afghanistan were and still serve as living examples of this.